2023
DOI: 10.3390/polym15122686
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Interface Strength in the Abaca-Fiber-Reinforced Bio-Polyethylene Composites

Abstract: Bio-based polymers, with any of their constituents based on nonrenewable sources, can answer the demands of society and regulations regarding minimizing the environmental impact. The more similar such biocomposites are to oil-based composites, the easier the transition, especially for companies that do not like the uncertainty. A BioPE matrix, with a structure similar to that of a high-density polyethylene (HDPE), was used to obtain abaca-fiber-reinforced composites. The tensile properties of these composites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…The result obtained for the fiber tensile strength factor ( FTSF ) for the coupled abaca-reinforced BioPE matrix in a previous publication was 100.89 [ 52 ]. The flexural strength factor ( FFSF ) is around 1.5 times higher than the tensile strength factor, with a value of 154.03, as was expected and published by previous authors [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The result obtained for the fiber tensile strength factor ( FTSF ) for the coupled abaca-reinforced BioPE matrix in a previous publication was 100.89 [ 52 ]. The flexural strength factor ( FFSF ) is around 1.5 times higher than the tensile strength factor, with a value of 154.03, as was expected and published by previous authors [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…The value of FTSF was obtained from a previous publication, being 100.89, and the value of FFSF was found before in this study, and it was 154.03. The value of was also established in a previous publication, and its mean value was 514.25 [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The volume fraction of abaca fibers contributed almost linearly to the composites' tensile strength, with maximum tensile properties achieved at 50 wt.% fiber loading. Moreover, it has been observed that the measures of mechanical properties increased in tandem with the weight fraction of abaca fibers and that the use of maleic acid as a coupling agent further improved these properties [64]. The development of bast-fiber composites by compression molding and chemically pretreating jute fibers with amino-silicone oil has been explored.…”
Section: Tensile Strength Flexural Strength and Impact Resistancementioning
confidence: 99%